1974
DOI: 10.1007/bf01436022
|View full text |Cite
|
Sign up to set email alerts
|

Enuresis, fire setting, and animal cruelty: A useful danger signal in predicting vulnerability of adolescent males to assaultive behavior

Abstract: Current shifts in corrective and rehabilitation planning result in an emphasis upon primary prevention efforts involving early identification and intervention with vulnerable children who run high risk of serious adolescent and adult delinquency. A variety of observers have argued that the presence of a combination of observable problem behaviors documented in childhood is related to ego weakness and may have value as a predictor of explosive acting out in later life. The present study examines a number of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
2

Year Published

1977
1977
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 5 publications
0
17
0
2
Order By: Relevance
“…Controversial associations of firesetting have been proposed. Enuresis may form an intracorrelated triad with firesetting and cruelty to animals (Heilman & Blackman, 1966), which is claimed to predict some adult aggressive crimes (Wax & Haddox, 1974). The 'sexual roots' of pyromania, which derived from highly selected observations that compulsive masturbation, impotence and fetishism were associated with fireraising (Schmid, 1914), have been recently reaffirmed in certain prison populations (Sapsford, Banks & Smith, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Controversial associations of firesetting have been proposed. Enuresis may form an intracorrelated triad with firesetting and cruelty to animals (Heilman & Blackman, 1966), which is claimed to predict some adult aggressive crimes (Wax & Haddox, 1974). The 'sexual roots' of pyromania, which derived from highly selected observations that compulsive masturbation, impotence and fetishism were associated with fireraising (Schmid, 1914), have been recently reaffirmed in certain prison populations (Sapsford, Banks & Smith, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Early research in this area focussed on a hypothesised triad of behaviours in children that appeared to be predictive of violence: enuresis, fire setting and cruelty to animals. [1][2][3] One review that supported a link between the predictors and interpersonal violence concluded that abusive acts to socially valued animals are more likely to be associated with interpersonal violence than are abuses of less socially valued animals. This association appears to be strongest among people who exhibit repeated acts of animal cruelty and recurrent violence against people.…”
mentioning
confidence: 99%
“…Traditionally, fire‐setting, along with animal cruelty and enuresis, has been seen as a marker of high risk to others in children (Wax & Haddox, 1974). An increased frequency of this combination of symptoms was reported more frequently in aggressive as opposed to non‐violent criminal offenders (Hellman & Blackman, 1966).…”
Section: Previous Historymentioning
confidence: 99%
“…Traditionally, fire-setting, along with animal cruelty and enuresis, has been seen as a marker of high risk to others in children (Wax & Haddox, 1974). An increased frequency of this combination of symptoms was…”
Section: Previous Historymentioning
confidence: 99%